2020
DOI: 10.3389/fendo.2020.609697
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Thyroid Tissues From Embryonic Stem Cells via Blastocyst Complementation In Vivo

Abstract: The generation of mature, functional, thyroid follicular cells from pluripotent stem cells would potentially provide a therapeutic benefit for patients with hypothyroidism, but in vitro differentiation remains difficult. We earlier reported the in vivo generation of lung organs via blastocyst complementation in fibroblast growth factor 10 (Fgf10), compound, heterozygous mutant (Fgf10 Ex1mut/Ex3mut) mice. Fgf10 also plays an essential role in thyroid development and branching morphogenesis, but any role thereof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Recently, Wen et al used intra-species blastocyst complementation to produce ESC-derived lungs and thyroids in Nkx2-1 -/mouse embryos lacking these tissues; interestingly, histological analysis of these embryos at E17.5 confirmed the efficient restoration of thyrocyte progenitor cells, expressing both NKX2-1/PAX8 (81). In a similar vein, Ran et al showed high thyroid contribution of donor ESCs and restoration of thyroid gland size and function in Fgf10 Ex1 mut /Ex3 mut mice that lack Fgf10 expression (82).…”
Section: Thyroid Gland Generation By Blastocyst Complementationmentioning
confidence: 81%
“…Recently, Wen et al used intra-species blastocyst complementation to produce ESC-derived lungs and thyroids in Nkx2-1 -/mouse embryos lacking these tissues; interestingly, histological analysis of these embryos at E17.5 confirmed the efficient restoration of thyrocyte progenitor cells, expressing both NKX2-1/PAX8 (81). In a similar vein, Ran et al showed high thyroid contribution of donor ESCs and restoration of thyroid gland size and function in Fgf10 Ex1 mut /Ex3 mut mice that lack Fgf10 expression (82).…”
Section: Thyroid Gland Generation By Blastocyst Complementationmentioning
confidence: 81%
“…This study demonstrated the limitations in using mutated genes expressing secreted factors in blastocyst complementation studies ( 28 ). Fgf10 mutant blastocysts were also used in another study to generate allogeneic thyroids that were largely, but not exclusively, derived from donor cells ( 29 ). An even more recent study used Nkx2-1 mutant embryos, which lack pulmonary and thyroid tissues.…”
Section: Blastocyst Complementation: Advancesmentioning
confidence: 99%
“… 56 Exosomes are promising in the cell-free therapeutic strategy for future studies. Recently, Wen et al 57 , 58 reported that mouse ESC complementation induces thyroid morphogenesis in Nkx2-1 −/− embryos (Nkx2-1 gene knockout embryos mice) and Fgf10 Ex1mut/Ex3mut mice (Fgf10 Ex1 genes mutation mice/Ex3 gene mutation mice). These generated tissues have normal morphology and physiological function.…”
Section: Msc-conditioned Culture Media Facilitates Regenerationmentioning
confidence: 99%